Battery degradation-aware current derating: an effective method to prolong lifetime and ease thermal management - Schimpe,M; Varela,Barreras J; Wu,B; Offer,GJ (Journal of The Electrochemical Society, 2021)
To ensure the safe and stable operation of lithium-ion batteries in battery energy storage systems (BESS), the power/current is de-rated to prevent the battery from going outside the safe operating range. Most derating strategies use static limits for battery current, voltage, temperature and state-of-charge, and do not account for the complexity of battery degradation. Progress has been made with models of lithium plating for fast charging. However, this is a partial solution, does not consider other degradation mechanisms, and still requires complex optimization work, limiting widespread adoption. In this work, the calendar and cycle degradation model is analysed offline to predetermine the degradation rates. The results are integrated into the current-derating strategy. This framework can be adapted to any degradation model and allows flexible tuning. The framework is evaluated in simulations of an outdoors-installed BESS with passive thermal management, which operates in a residential photovoltaic application. In comparison to standard derating, the degradation-aware derating achieves: (1) increase of battery lifetime by 65%; (2) increase in energy throughput over lifetime by 49%, while III) energy throughput per year is reduced by only 9.5%. These results suggest that the derating framework can become a new standard in current derating.